An Overview of Argumentation Frameworks for Decision Support - Carstens, Lucas; Fan, Xiuyi; Gao, Yang; Toni, Francesca (Graph Structures for Knowledge Representation and Reasoning, 2016)
Several forms of argumentation frameworks have been used to support decision-making: these frameworks allow at the same time a graphical representation of decision problems as well as an automatic evaluation of the goodness of decisions. We overview several such uses of argumentation frameworks and discuss future directions of research, including cross-fertilisations amongst them.